PENGARUH HARTA DAN BIAYA USAHA TERHADAP EFISIENSI FINANSIAL PADA KOPERASI DI KOTA BANGKINANG - Maiwinda Sari, Rafiska Maiwinda Sari Rafiska; ', Suarman; ', Ngadlan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This study aims to determine whether there is influence between assets and business costs for financial efficiency in cooperative BangkinangCity . This research was conducted in April 2014. The study population was cooperative in the town Bangkinang totaling 65 Cooperative , but who have complete data for this study , there are 16 units of cooperatives in the Department of City District Cooperative Bangkinang . Processing the data using SPSS 16.0 . The amount of influence on the efficiency of financial variables simultaneously is equal to 0.181 , while the influence of business costs simultaneously at 0,118 . The rest was influenced by other factors not examined in this study . And the influence of business expenses against the financial efficiency of 0.03 . The point is that the financial efficiency is influenced by wealth and business costs , this indicates that the property and the cost to the cooperative efforts in the City Bangkinang must be considered as having an influence on the financial efficiency in cooperative Bangkinang City . The multiple regression equation obtained was Y = 15.997 + 0,426X1 + 0,344X2Â Keywords :Property , Business Costs , Efficiency Finance Â  Â